THE EFFECTIVENESS OF THE USE OF VIDEO TUTORIALS AS A MEDIUM OF LEARNING TOWARDS A LEARNING OUTCOMES COMPETENCIES MASTERED BASIC STOP-MOTION ANIMATION (FLAT AREAS) STUDENTS OF SMK NEGERI 2 PAREPARE - Yunendar, Wakhid (Patria Artha Technological Journal, 2017)
This research aims to know the effectiveness of video tutorials learning results against students of SMK Negeri 2 Parepare on standards of competence to master the basic stop-motion animation (flat areas). This research is quasi experimental research of Non-equivalent Control Group Design. The population of the research was the class majoring in multimedia competency standards studied master basic stop-motion animation (flat areas) in SMK Negeri 2 Parepare years lessons 2013/2014. Data collection techniques used are engineering tests. Data analysis techniques used are descriptive and inferensial. Results of the study it was concluded that: the effectiveness of the use of media video tutorial is higher than using conventional learning media. This is demonstrated by the posttes hypothesis test where the value t calculate > t table (12.733 > 2.000) then the Ho in decline. So it can be concluded that there is a difference between a class with media video tutorials and classes that do not use the video tutorial with an average increase in value of 43.9 alphabets experiment classes and control classes of 21.74 so results the students learn to use media video tutorials are better than on the results of the learning of students who are not using the media of video tutorials in class XI Multimedia SMK Negeri 2 mastering basic competency Parepare animated stop-motion (flat areas) . Conclusion based on the results of the research are advised: Video tutorial is one of the alternative media interactive learning that develop creative attitude, then we recommend this learning media can be used in multimedia-based learning.Â